2019
DOI: 10.3389/fpls.2019.01609
|View full text |Cite
|
Sign up to set email alerts
|

AtDAT1 Is a Key Enzyme of D-Amino Acid Stimulated Ethylene Production in Arabidopsis thaliana

Abstract: D-Enantiomers of proteinogenic amino acids (D-AAs) are found ubiquitously, but the knowledge about their metabolism and functions in plants is scarce. A long forgotten phenomenon in this regard is the D-AA-stimulated ethylene production in plants. As a starting point to investigate this effect, the Arabidopsis accession Landsberg erecta (Ler) got into focus as it was found defective in metabolizing D-AAs. Combining genetics and molecular biology of T-DNA insertion lines and natural variants together with bioch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
(105 reference statements)
0
12
0
Order By: Relevance
“…This class also contains the non-AT enzyme 4-amino-4-deoxychorismate lyase that is involved with folate biosynthesis. Interestingly, Arabidopsis d -amino acid AT also exhibits 4-amino-4-deoxychorismate lyase activity ( 122 , 123 ).…”
Section: Evolution Of Four Classes Of At Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…This class also contains the non-AT enzyme 4-amino-4-deoxychorismate lyase that is involved with folate biosynthesis. Interestingly, Arabidopsis d -amino acid AT also exhibits 4-amino-4-deoxychorismate lyase activity ( 122 , 123 ).…”
Section: Evolution Of Four Classes Of At Enzymesmentioning
confidence: 99%
“…Arabidopsis DAAT is the major AT involved in metabolism of d -amino acids, which stimulate ethylene production through unknown mechanisms ( 123 ). Arabidopsis DAAT prefers d -methionine among many other d -amino acid substrates that can be used and utilizes both pyruvate and, to a lesser extent, α-ketoglutarate as amino acceptors (forming d -alanine and d -glutamate, respectively) ( 123 , 316 ). Arabidopsis DAAT also functions as 4-amino-4-deoxychorismate lyase for the synthesis of a folate precursor, aminobenzoate ( 122 ).…”
Section: Functional Diversification Of At Enzymesmentioning
confidence: 99%
“…We believe that multiple specialised enzymes exist to process d ‐amino acids and ACC. This theory is supported by a recent observation in Arabidopsis, in which d ‐amino acid transaminase 1 (DAT1) was shown to have a specialised role in d ‐amino acid metabolism (Suarez et al ., 2019). DAT1 is able to transaminate d ‐methionine into d ‐alanine, d ‐glutamic acid and l ‐methionine.…”
Section: Regulation Of Ethylene Biosynthesis By D‐amino Acidsmentioning
confidence: 99%
“…DAT1 is able to transaminate d ‐methionine into d ‐alanine, d ‐glutamic acid and l ‐methionine. The dat1 loss of function mutant showed an increased d ‐amino‐acid‐stimulated ethylene production compared with wild‐type plants when fed d ‐methionine (Suarez et al ., 2019). The authors also showed that this increase in ethylene production is not caused by a reduced malonylation of ACC, as both malonylated d ‐methionine (malonyl‐ d ‐methionine) and ACC (MACC) levels were higher in dat1 mutants (Suarez et al ., 2019).…”
Section: Regulation Of Ethylene Biosynthesis By D‐amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation